Livestock guardian dogs: introduction, and a summary of training advice - Hankins, Jeff; Hankins, Conny (Countryside and small stock journal (1985), 1997)
A variety of livestock guarding dog breeds are marketed. A guide to the purchase, training, and treatment of such dogs is provided via a case study of a Turkish Akbash dog. Several reference books and information sources are also provided.